Is Employee Engagement Really Impact on Turnover Intention - Fawzia Nurmadina Arifany; Kiki Sudiana (Universitas Mercu Buana, 2026)
Objectives: Employee engagement is often considered one of the factors that can reduce turnover intention. The inconsistency of the results indicates that there are various variations depending on the industry context and the conditions of the job and the company. In the EPC (Engineering, Procurement, and Construction) industry, this challenge becomes increasingly complex due to the high pressure to meet project deadlines, dynamic work environments, and rapid project rotations, which can significantly affect employee engagement and turnover intention. In National Construction Company experiencing financial crises due to project failures resulting from the implementation of PSAK-72 and the conditions of COVID-19, this leads to uncertainty in project sustainability, prompting many employees to leave the company. This research consists of two variables, employee engagement as the independent variable and turnover intention as the dependent variable. The study aims to determine whether employee engagement has an effect on turnover intention.Methodology: The method used in this research is analysis, with data collection through questionnaires. This research employs a quantitative method with a non-probability sampling technique of convenience sampling. The population in this study is all employees at the National Construction Company, totaling 676. A sample of 251 employees was selected for analysis in this research. The data analysis techniques used are descriptive analysis, classical assumption tests, multiple linear regression analysis, and hypothesis testing.Finding: The results of this study indicate that employee engagement has a significant effect on turnover intention among employees of the National Construction Company.Conclusion: The results of this research are expected to be utilized by the management of the National Construction Company to reduce turnover rates by considering the employee engagement perceived by employees, thereby enabling the company to achieve better and sustainable performance.